PRAGMATIC VALUES IN MASTERING SYNONMYS FOR BETTER EXPRESSION - Albina Bazarbaeva (Western European Studies, 2024)
This article examines the pragmatic values in mastering synonymy for better expression. The most important pragmatic functions of synonyms are their ability to express the degree of intensity of an action, shift semantic accents in the nominated concept, and mask undesirable tendencies and events through contextual synonyms or euphemization. Synonyms are often considered as a rhetorical means of achieving the speaker's pragmatic task. The results of the study reveal the complexity of synonymy as a linguistic phenomenon
Keywords: synonym; semantics; function; pragmatic values